2020
DOI: 10.2147/dmso.s238247
|View full text |Cite
|
Sign up to set email alerts
|

<p>Association Between Cognitive Impairment and Blood Pressure Among Patients with Type II Diabetes Mellitus in Southern Iran</p>

Abstract: Purpose: Both type 2 diabetes mellitus (T2DM) and hypertension are regarded as lifethreatening diseases known to be risk factors for vascular diseases. They may be associated with the increased risk of cognitive impairment (CI), although there are conflicting data relating hypertension to the risk of CI. Therefore, this study aimed to explore the probable association between hypertension and CI in patients with T2DM. Patients and Methods: This cross-sectional study assessed the degree of CI of a total of 350 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
(46 reference statements)
1
6
0
Order By: Relevance
“…Participants who knew their hypertensive status were less likely to develop cognitive impairment when compared to their counterparts in the study who do not know their hypertensive status. An Iranian study by similar, to our finding demonstrated an Open Access Journal of Gerontology & Geriatric Medicine association between hypertension and cognitive impairment [50]. Participants who knew their hypertensive status are more likely to take medication for blood pressure control and ameliorate the effect of hypertension in the development of cognitive impairment.…”
Section: Hypertensionsupporting
confidence: 80%
“…Participants who knew their hypertensive status were less likely to develop cognitive impairment when compared to their counterparts in the study who do not know their hypertensive status. An Iranian study by similar, to our finding demonstrated an Open Access Journal of Gerontology & Geriatric Medicine association between hypertension and cognitive impairment [50]. Participants who knew their hypertensive status are more likely to take medication for blood pressure control and ameliorate the effect of hypertension in the development of cognitive impairment.…”
Section: Hypertensionsupporting
confidence: 80%
“…With the dysfunction of flow autoregulation, it is postulated that the elimination of potentially harmful proteins such as beta-amyloid is limited, which it is worth mentioning has been found in higher concentrations in these patients. In addition, evidence of structural changes in neuroimaging associated with the increase in systolic blood pressure has been found, with a lower cerebral volume in these patients 11,33 .…”
Section: Discussionmentioning
confidence: 87%
“…The findings were not consistent with previous study (12) due to the different geographical locations and characteristics of the study participants. Despite chronic diseases such as hypertension and diabetes mellitus type II were reported to be associated factors for the development of cognitive impairment (18), it was found that there was no significant association between chronic disease and cognitive impairment.…”
Section: Discussionmentioning
confidence: 95%